Human Resource Development Oriented Performance Appraisal System in Armed Police Force, Nepal - Paudel, Suraj (Journal of APF Command and Staff College, 2023)
Human Resource Management (HRM) involves managing and developing the workforce, while Human Resource Development (HRD) optimizes performance, fosters growth, and aligns HR practices with employee needs. Performance Appraisal (PA) is vital for HRD, identifying strengths, development areas, fostering growth, and optimizing organizational performance. The research employed a descriptive design with a sequential explanatory method, gathering quantitative data from 74 and qualitative data from 25 respondentsout of 1741 officers in the Armed Police Force, Nepal (APF). Both descriptive and inferential statistics were used to examine the quantitative data as well as thematic analysis was executed for the qualitative analysis to study the performance appraisal system in the APF focusing on its alignment with HRD principles. The study reveals that the APF has an HRD climate and is oriented towards HRD principles in its performance appraisal system. However, significant improvements are needed to enhance the system's effectiveness and fairness. The study further highlights the importance of the monitoring on performance appraisal process and linking performance appraisal results with other HRD mechanisms for a comprehensive HRD-oriented PA system. The research suggests implementing training for appraisers, improving performance review frequency, and incorporating potential appraisal, adopting a more systematic and objective evaluation system to foster a fair and growth-oriented appraisal environment. These findings have significant applications for enhancing the PA system and promoting HRD within the organization since the study emphasized the importance of a strong monitoring system, regular feedback, and potential appraisal to foster an HRD-oriented appraisal process, ultimately promoting employee growth and organizational development.